A Randomized Trial of Split Dose 3 L Polyethylene Glycol Lavage Solution, 2 L Polyethylene Glycol Lavage Combined With Castor Oil, and 1 L of Polyethylene Glycol Lavage Solution Combined With Castor Oil and Ascorbic Acid for Preparation for Colonoscopy - Tian, Xu; Shi, Bing; Liu, Xiao-Ling; Chen, Hui; Chen, Wei-Qing (Frontiers in Medicine, 2019)
Background: Castor oil (CaO) has the potential of halving the required volume of bowel preparation solution; however, no clinical trial investigated the efficacy of CaO on bowel preparation for colonoscopy in addition to polyethylene glycol (PEG). Objectives: Our aim was to evaluate efficacy and safety of lower dose PEG together with 30 mL CaO alone or plus ascorbic acid (Asc) in bowel preparation before colonoscopy. Methods: Two hundred and forty-six patients were allocated randomly to ingest 2 L PEG with 30 mL CaO, 1 L PEG with 30 mL CaO plus 5 g Asc, or 3 L PEG. We used Boston Bowel Preparation Scale (BBPS) to evaluate bowel preparation efficacy. We also determined other outcomes such as procedure time, polyp or adenoma detection rate, and adverse events (AEs). Results: Of 282 patients recruited, 36 were excluded. Groups were matched for baseline characteristics except weight (P = 0.020) and body mass index (BMI) (P = 0.003). Patient's satisfaction was higher in 2 L PEG-CaO (P = 0.016) and 1 L PEG-CaO-Asc groups (P = 0·017). Patients' compliance was 67.5, 71.4, and 80.5% in 3 L PEG, 2 L PEG-CaO, and 1 L PEG-CaO-Asc groups (P = 0.014). Adequate bowel preparation rate was 75, 78.57, and 53.66% in 3 L PEG, 2 L PEG-CaO, and 1 L PEG-CaO-Asc groups (P = 0.021). There were no differences in terms of remaining outcomes. Conclusions: Despite an increase in patients' satisfaction and compliance, 1 L PEG-CaO-Asc significantly decreased adequate bowel preparation rate. However, 2 L PEG-CaO improved the patients' satisfaction and compliance and increased adequate bowel preparation rate (Registration number, ChiCTR-IIR-17012418).